2017
DOI: 10.1186/s13013-017-0139-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Schroth exercises during bracing in adolescent idiopathic scoliosis: results from a preliminary study—SOSORT Award 2017 Winner

Abstract: BackgroundBracing has been shown to decrease significantly the progression of high-risk curves to the threshold for surgery in patients with adolescent idiopathic scoliosis (AIS), but the treatment failure rate remains high. There is evidence to suggest that Schroth scoliosis-specific exercises can slow progression in mild scoliosis. The aim of this study was to evaluate the efficacy of Schroth exercises in AIS patients with high-risk curves during bracing.MethodsA prospective, historical cohort-matched study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(128 citation statements)
references
References 24 publications
(24 reference statements)
4
111
0
13
Order By: Relevance
“…Schroth group had improvement also in other variables of SRS-22r: pain=18.4%, function=28.6%, with decrease of SRS-22r total in 0.08 (p=0.047), also there was improvement in the results of SAQ instrument (Schreiber et al, 2015). Kwan, Cheng, Koh, Chiu and Cheung (2017) also reported that application of Schroth method showed significant improvement in function and in total score, while in other domains they reported that there was signifi cant diff erence in experimental group, while in control group they didn't fi nd signifi cant improvement in none of SRS-22 domains. For evaluation of the QoL, these authors used SRS-22 instrument.…”
Section: Discussionmentioning
confidence: 86%
“…Schroth group had improvement also in other variables of SRS-22r: pain=18.4%, function=28.6%, with decrease of SRS-22r total in 0.08 (p=0.047), also there was improvement in the results of SAQ instrument (Schreiber et al, 2015). Kwan, Cheng, Koh, Chiu and Cheung (2017) also reported that application of Schroth method showed significant improvement in function and in total score, while in other domains they reported that there was signifi cant diff erence in experimental group, while in control group they didn't fi nd signifi cant improvement in none of SRS-22 domains. For evaluation of the QoL, these authors used SRS-22 instrument.…”
Section: Discussionmentioning
confidence: 86%
“…The PEDro scale was ranked from 5 to 9, with an average score of 6.9/10 for overall articles (Table 1). Speci cally, the average scores of Schroth studies (35)(36)(37)(38)45), scienti c exercise approach to scoliosis (SEAS) studies (41,47,48), and alternative SSE(40, 46) studies were 6.4 (n=5, score: 5-8), 8 (n=3, score: 8-9), and 6.5 (n=2, score: 6-7), respectively. Criteria 4 (blinding subjects) and 5 (blinding therapists) were not met for 80% (n=8) of studies (35)(36)(37)(38)(45)(46)(47)(48).…”
Section: Evidence Hierarchy and Methodological Appraisalmentioning
confidence: 99%
“…Two studies showed better improvement of ATR in the study group (37,41). For QoL (Table 3), ve studies adopted the SRS-22 questionnaire (38,41,(46)(47)(48), and one study adopted the SRS-23 questionnaire (37). However, a high initial score (mean score: 3.8-4.2) was noted in all studies (Table 3), with three studies reporting better QoL outcomes in terms of function and mental domain, favoring the SSE group (41,46,48).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations